2005
DOI: 10.1056/nejmoa033349
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Storage Diseases Presenting as Hypertrophic Cardiomyopathy

Abstract: LAMP2 mutations typically cause multisystem glycogen-storage disease (Danon's disease) but can also present as a primary cardiomyopathy. The glycogen-storage cardiomyopathy produced by LAMP2 or PRKAG2 mutations resembles hypertrophic cardiomyopathy but is distinguished by electrophysiological abnormalities, particularly ventricular preexcitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
417
4
51

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 578 publications
(485 citation statements)
references
References 27 publications
13
417
4
51
Order By: Relevance
“…Similarly, previous studies have shown glycogen storage diseases mimicking HCM with mutations in PRKAG2-encoding protein kinase gamma 2 and LAMP2-encoding lysosome-associated membrane protein 2 [19]. Compared to myofilament-HCM, both Z-disc-and metabolic-HCM account for a relatively small percentage of HCM leaving a significant proportion of HCM genetically unexplained.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similarly, previous studies have shown glycogen storage diseases mimicking HCM with mutations in PRKAG2-encoding protein kinase gamma 2 and LAMP2-encoding lysosome-associated membrane protein 2 [19]. Compared to myofilament-HCM, both Z-disc-and metabolic-HCM account for a relatively small percentage of HCM leaving a significant proportion of HCM genetically unexplained.…”
Section: Introductionmentioning
confidence: 52%
“…Recent discoveries have implicated several genes encoding components of the Z-disc as well as genes previously associated with dilated cardiomyopathy in the pathogenesis of HCM [19,31,32]. This paper reports the discovery of S101R, Y141H, and S165F mutations in JPH2 as a novel genetic basis for HCM.…”
Section: Discussionmentioning
confidence: 85%
“…Given the key role of GSK-3 in regulating glycogen storage, we asked whether enhanced glycogen storage, which leads to cardiac hypertrophy in patients with mutations in the γ 2 subunit of AMPK (22), could account for the hypertrophy in the Gsk3a -/-mice. Although we did find that GSK-3α regulated phosphorylation status of the critical Ser641 residue of glycogen synthase ( Figure 1C) and, consequently, glycogen storage in the heart, the absolute amount of glycogen in the heart was small (0.05% of that in the liver), and the increase compared with WT littermates was minimal (12.5 ± 0.36 vs. 15.7 ± 0.95 mg/g of tissue; P = 0.06).…”
Section: Hypertrophy In the Gsk-3α Komentioning
confidence: 99%
“…Findings in the proband's mother illustrate that the later stages of illness are sufficiently destructive that characteristic findings may not be readily apparent. In light of the surprisingly high sample prevalence of 6/ 75 (8%) and 3/50 (6%) of LAMP2 mutations in two recent molecular screens of unselected hypertrophic cardiomyopathy patients (Arad et al 2005;Cheng et al 2012), a high index of suspicion for this condition is warranted, and routine screening using a combination of methods appears appropriate.…”
Section: Discussionmentioning
confidence: 99%